Pengaruh Nilai Tukar Rupiah dan BI Rate Terhadap Harga Saham Sektor Basic Materials pada IDX MES BUMN 17 Periode 2021-2023 - Afiyah; Nihayatul Maskuroh; Erdi Rujikartawi (Economic Reviews Journal, 2024)
This research aims to test the rupiah exchange rate and BI Rate variables on basic materials sector stock prices on IDX MES in the long term and short term using the Vector Error Correction Model (VECM) analysis method in the Eviews 11 application. The data used is monthly in January 2021 -December 2023 sourced from Bank Indonesia and the Indonesian Stock Exchange. The results obtained are in accordance with the VECM test, the rupiah exchange rate variable in the short term and long term has a significant negative effect on stock prices, while the BI Rate variable in the short term and long term has no significant effect on stock prices. Based on the causality test, the rupiah exchange rate and BI There is no two-way causal relationship between rates and share prices.